2016
DOI: 10.3892/mmr.2016.5442
|View full text |Cite
|
Sign up to set email alerts
|

The angiogenic effect of dracorhodin perchlorate on human umbilical vein endothelial cells and its potential mechanism of action

Abstract: Hyperglycemia is the key clinical feature of diabetes, and may induce refractory wound lesions and impaired angiogenesis. Dracorhodin perchlorate (Dra) is the major ingredient of dragon's blood and it has been used as a medicine to treat chronic wounds, such as diabetic foot, since ancient times in many cultures. The current study aimed to investigate the effect of Dra on human umbilical vein endothelial cells (HUVECs) under high‑glucose (HG) stimulation and its potential mechanism. Dra was observed to increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Recent research has demonstrated that DP promotes vascular endothelial cell proliferation and angiogenesis to accelerate wound healing [20]. However, research on whether DP can promote fibroblast proliferation has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has demonstrated that DP promotes vascular endothelial cell proliferation and angiogenesis to accelerate wound healing [20]. However, research on whether DP can promote fibroblast proliferation has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Dracorhodin perchlorate is an artificial synthetic analogue of dracorhodin, which is widely used as a high‐performance liquid chromatography (HPLC) standard and for investigating the biological activities of dracorhodin. Its in vitro angiogenic activity on HUVEC cells, in vivo angiogenic activity on zebrafish embryos, and wound healing activity on rats have been reported previously . Thin‐layer chromatography (TLC)‐ and HPLC‐based methods are well established to examine commercial dragon blood samples .…”
Section: Introductionmentioning
confidence: 96%
“…Its in vitro angiogenic activity on HUVEC cells, in vivo angiogenic activity on zebrafish embryos, and wound healing activity on rats have been reported previously. [7][8][9] Thin-layer chromatography (TLC)-and HPLC-based methods are well established to examine commercial dragon blood samples. 6,10 However, HPLC analysis is time-consuming and TLC-based methods are not ideal for routine examination of large amounts of commercial product samples.…”
Section: Introductionmentioning
confidence: 99%
“…D.P has multiple applications in medicine, for example, D.P is found to enhance cutaneous wound healing by promoting fibroblasts proliferation in rats . D.P also exerts strong angiogenic effects, which can be beneficial for wound healing . D.P is found to have an anti‐cancer function by inducing apoptosis in human cancer cells .…”
Section: Introductionmentioning
confidence: 99%
“…4,5 D.P also exerts strong angiogenic effects, which can be beneficial for wound healing. 6,7 D.P is found to have an anti-cancer function by inducing apoptosis in human cancer cells. [8][9][10][11][12] Reported in some other literatures, D.P has anti-microbial effects by reducing the production of α-toxin by Staphylococcus aureus 13 and inhibiting the formation of biofilm and virulence factors of Candida albicans.…”
Section: Introductionmentioning
confidence: 99%